1976
DOI: 10.1029/rg014i001p00013
|View full text |Cite
|
Sign up to set email alerts
|

Vertical crustal movements from leveling data and their relation to geologic structure in the eastern United States

Abstract: Through analysis of leveling data, rates of relative vertical motion have been determined for points of a grid of profiles over much of the eastern United States. The rates are commonly too large to be attributed to leveling errors and therefore must reflect true earth movements. With some exceptions, modern movements appear to be related to earlier Phanerozoic trends, but the rates of modern movements are much larger than average rates over the past 130 m.y. Thus movements are either episodic or oscillatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 84 publications
1
46
0
Order By: Relevance
“…Absolute rates of crustal movement can be determined only if the leveling net is tied into a fixed frame of reference, usually tide-gauge stations (e.g., Holdahl and Morrison, 1974;Vanicek, 1975Vanicek, , 1976. Leveled surfaces are warped to fit the tide-gauge data, which can introduce errors due to nonsynchronous leveling and tide-gauge data, as well as excessive smoothing (Brown and Oliver, 1976 Leveling data are not without error. Constant relative movement over the time interval between relevelings is assumed, although various studies have shown that this assumption is not always correct (e.g., Brown and Oliver, 1976;Brown, 1978).…”
Section: Geologic Influencementioning
confidence: 99%
“…Absolute rates of crustal movement can be determined only if the leveling net is tied into a fixed frame of reference, usually tide-gauge stations (e.g., Holdahl and Morrison, 1974;Vanicek, 1975Vanicek, , 1976. Leveled surfaces are warped to fit the tide-gauge data, which can introduce errors due to nonsynchronous leveling and tide-gauge data, as well as excessive smoothing (Brown and Oliver, 1976 Leveling data are not without error. Constant relative movement over the time interval between relevelings is assumed, although various studies have shown that this assumption is not always correct (e.g., Brown and Oliver, 1976;Brown, 1978).…”
Section: Geologic Influencementioning
confidence: 99%
“…The 1973 Point Mugu quake (6.0) was preceded by uplifting and then downwarping of about 4 cm during the previous 13 years [Castle et al, 1977]. However, these changes are not remarkably bigger than those inferred from leveling data in relatively non-seismic regions [Brown, 1976], and more recent experience with the Palmdale bulge has indicated that leveling must be treated with care and used in combination of other data [Kumar & Strange, 1978]. This data should include both gravity measurements and horizontal geodetic survey.…”
Section: Earthquakesmentioning
confidence: 99%
“…Postseismic geodetic measurements [e.g., Brown et al, 1977] are important because they indicate some aspects of the stress redistribution precursory to subsequent creep and seismicity in the zone, and because they are affected by the same tectonic context as the earthquake itself. In fact, so far earthquake models have been more successful in explaining post-seismic adjustment than the precursory buildup and the earthquake itself [e.g., Nur & Mavko, 1974;Anderson, 1975;Rundle & Jackson, 1977;Walcott, 1978].…”
Section: Earthquakesmentioning
confidence: 99%
“…These observations need to be validated because they do not accord with geological evidence, although they do accord with the expected effect of atmospheric refraction when repeat leveling surveys are made over shorter sight lengths than was common in earlier times. Present rates of uplift relative to the Atlantic coastal plain, according to sparse geodetic data, are up to 6 mm/yr (Brown and Oliver, 1976), whereas erosion rates from Late Cenozoic time to present yield a geological uplift rate of only about x.04 mm/yr (Hack, 1978). According to Isachsen (1976a;197Gb) and Isaensen et al ( 1978), the Adirondack Mountains are doming upward at the late of 3-4 mm/yr during Holocene time, whereas tide-gauge levels on Lake Champlain just east of the dome register no more than 1 mm/yr in historic time, contradicting the leveling estimates (Barnett and Isachsen, 1980).…”
mentioning
confidence: 99%
“…Compilations of vertical data on a national scale (Brown and Oliver, 1976;Gable and Hatton, 1980) indicate that major crustal movements are taking place far from the recognized boundaries of the North American plate-movements that are seemingly unrelated to plate-tectonic processes, at least insofar L-we understand them at present. Other movements can be attributed to plate tectonics, but the details are not understood.…”
mentioning
confidence: 99%